Cannabinoid Hyperemesis Syndrome - Jaikla, Kriengsak; Chimplee, Kaset (Greater Mekong Subregion Medical Journal, 2024)
Cannabinoid Hyperemesis Syndrome (CHS) is a condition characterized by cyclic episodes of nausea and vomiting, abdominal pain, and relief of symptoms by taking of hot shower, this syndrome being associated with chronic cannabis use. CHS occurs in approximately one-third of individuals presenting with cannabis use disorder. The pathophysiology of CHS is not fully understood, but it is believed to involve the endocannabinoid system (ECS). This report describes an 18-year-old female, with a history of marijuana consumption spanning nearly two years, who presented with intense nausea and vomiting. The patient made a complete recovery following cannabis abstinence and supportive treatment. Two months follow-up revealed a full resolution of the symptoms.